Evaluation Of Rehabilitation / Construction Of Irrigation Projects In West Of Sulaimani City - Aziz, Salahaddin A.; Qadir, Kamal Sh. (Sulaimani Journal for Pure and Applied Sciences, 2013)
This study was conducted to assess agricultural and irrigation projects in some locations of Sulaimani governorate were abandoned and the expulsion of its inhabitants because of political circumstances and brought them together in other areas. After the collapse of the Baath regime in Iraq and formation of parliamentary system of rule, led to the return of these families to their fields and that the humanitarian organizations and international collaborators in the re-rehabilitation of irrigation projects and construction, In this study, 13 irrigation projects were selected and questionnaires have been distributed to the peasants, and also visited the departments of agricultural to obtain information about the reality of agricultural production. The results showed, that the channels repaired by concrete led to minimization of evaporation and leakage of them have increased the quantity of irrigation water and for this reason the level of living of farmers was raised in terms of increased agricultural production. With regard to the size of the channels, the results showed that the size of channels was not enough to fulfill the amount of rainfall. Also most of the farmers were dependent on the cultivation of crops with a high value in the market. The results also showed that the lack of irrigation water in some projects was due to the lack of distribution channels and structures in some areas.
Keywords: irrigation projects; Evaluation; Rehabilitation